Muslim Household Debt Behavior in Urban Indonesia Descriptive Evidence from the City of Depok - Nasiha Sakina Ramadhanikar; Qurroh Ayuniyyah; Ibdalsyah Ibdalsyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Debt Acquisition is an unavoidable of household financial life. In Islamic teachings, debt is permissible but should be treated as a last resort, undertaken only after careful consideration of priority needs. Islamic economic principles emphasize that needs should be directed toward achieving the objectives of aqashid al-sharia, which are hierarchically classified into essential (dharuriyyat), complementary (hajiyyat), and luxury (tahsiniyat) needs. Understanding how these principles are reflected in actual household debt behavior is therefore important. This study aims to describe patterns of debt among Muslim households in the City of Depok, Indonesia. Using primary survey data collected in 2022, the study applies quantitative descriptive analysis to examine household debt behavior. The analysis focuses on the purposes of debt and the types of needs that household debt behavior is intended to fulfill, without testing causal relationship. The results indicate that debt patterns of Muslim household in the city of Depok generally reflect prudent financial behavior. Most borrowing is undertaken to meet essential (dharuriyyat) needs, particularly for first home, education expenses, first vehicle ownership, and the fulfillment of basic household necessities. These findings suggest that household debt in this urban Muslim context is predominantly necessity-driven rather than consumption-oriented. This study provides baseline empirical evidence on Muslim household debt behavior and contributes to the literature on Islamic household finance by offering a descriptive snapshot that can support future explanatory and comparative research